Decoding Drug Interactions: Character and Degree of Pharmacokinetic Interactions Between Telmisartan and Sorafenib or Donafenib in Rats - Li Y; Du W; Shan C; Yu Z; An J; Dong Z (Drug Design, Development and Therapy)
Ying Li,1,2,* Wenyu Du,1– 3,* Chunhui Shan,4 Zefang Yu,1 Jing An,1,2 Zhanjun Dong1,2 1Department of Pharmacy, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of China; 2Hebei Key Laboratory of Clinical Pharmacy, Shijiazhuang, Hebei, People’s Republic of China; 3Graduate School of Hebei Medical University, Shijiazhuang, Hebei, People’s Republic of China; 4Department of Medical Imaging, Hebei General Hospital, Shijiazhuang, Hebei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhanjun Dong, Email dzjhbgh@126.comBackground: Sorafenib and lenvatinib play a significant role as small molecule targeted drugs in the treatment of advanced hepatocellular carcinoma. However, both drugs are most commonly associated with hypertension as a side effect, frequently needing antihypertensive treatment. Telmisartan, an antagonist of angiotensin II receptor, can attenuate sorafenib- or donafenib-induced hypertension. In clinical settings, sorafenib or donafenib is often prescribed alongside telmisartan, but the pharmacokinetic interactions between donafenib and telmisartan, as well as sorafenib and telmisartan, are not well understood. Therefore, this study aimed to evaluate these pharmacokinetic interactions in male Sprague-Dawley (SD) rats.Methods: The animals were divided into seven groups (n = 6) and treated with sorafenib, donafenib, or telmisartan as monotherapy (groups I–III), multi-dose sorafenib or donafenib with single dose telmisartan (groups IV and V), or multi-dose telmisartan with single dose sorafenib or donafenib (groups VI and VII). The levels of drugs in rat plasma were quantified using ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS).Results: Multiple doses of donafenib resulted in a 0.97-fold (P=0.010) increase in the area under the plasma concentration–time curve (AUC) of telmisartan and a 57.3% (P=0.038) and 45.6% (P=0.032) decrease in the apparent clearance (CLz/F) and the apparent volume of distribution (Vz/F) of telmisartan, respectively. Telmisartan resulted in a decrease in donafenib exposure; however, this effect was not statistically significant. The pharmacokinetic characteristics of sorafenib were significantly altered when it was co-administered with telmisartan. In particular, the AUC value and the maximum plasma concentration (Cmax) increased by 77.7% (P< 0.001) and 60.9% (P< 0.001), respectively, whereas Vz/F (50.4%, P=0.008) and CLz/F (46.0%, P=0.006) were significantly decreased. However, sorafenib did not affect the pharmacokinetic characteristics of telmisartan.Conclusion: The results demonstrated potential interactions between telmisartan and sorafenib or donafenib, which may guide dosage adjustment and prevent toxic effects in individual patients.Keywords: hepatocellular carcinoma, hypertension, donafenib, telmisartan, sorafenib, pharmacokinetics, drug–drug interactions